Ileal Perforation Caused by Pleural Mesothelioma-related Small Intestinal Involvement: A Case Report and Literature Review. - WANG, Yunjia; SHEN, Fangqian; LI, Qisha; LI, Xinjuan; YANG, Hua; LIU, Puyu; YANG, Xuefeng; ZHANG, Nianjie; ZHOU, Jianguo; BAI, Yuju (Chinese Journal of Lung Cancer, 2026)
Pleural mesothelioma (PM) usually manifests as local intrathoracic invasion, and small intestinal involvement is rare. A 37-year-old man with initially diagnosed stage IV diffuse PM and no definite history of asbestos exposure or other specific occupational or environmental exposure except for long-term smoking was reported. After first-line treatment with Pemetrexed, Carboplatin and Bevacizumab, the disease remained stable. However, acute abdomen occurred during maintenance therapy, and emergency surgery confirmed terminal ileal perforation. Postoperative pathology suggested PM-related ileal involvement/metastatic involvement, with a higher Ki-67 proliferation index than that of the primary lesion. Because only perforation repair rather than segmental bowel resection was performed, the available pathological material could not determine whether full-thickness bowel-wall involvement was present or the direction of tumor invasion. Imaging findings, intraoperative findings and pathological results did not support primary peritoneal mesothelioma or direct contiguous invasion of the ileum by the diaphragmatic lesion; however, microscopic peritoneal dissemination with secondary bowel-wall involvement could not be completely excluded. The aim of this report, together with literature review, is to summarize the diagnostic challenges, management strategies and clinical implications of PM-related small intestinal involvement.